Predicting device failure after percutaneous repair of functional mitral regurgitation in advanced heart failure: Implications for patient selection. (15th April 2018) - Stolfo, Davide; De Luca, Antonio; Morea, Gaetano; Merlo, Marco; Vitrella, Giancarlo; Caiffa, Thomas; Barbati, Giulia; Rakar, Serena; Korcova, Renata; Perkan, Andrea; Pinamonti, Bruno; Pappalardo, Aniello; et al.
Abstract: Background: Patients with heart failure (HF) and severe symptomatic functional mitral regurgitation (FMR) may benefit from MitraClip implantation. With increasing numbers of patients being treated the success of procedure becomes a key issue. We sought to investigate the pre-procedural predictors of device failure in patients with advanced HF treated with MitraClip. Methods: From April 2012 to November 2016, 76 patients with poor functional class (NYHA class III–IV) and severe left ventricular (LV) remodeling underwent MitraClip implantation at University Hospitals of Trieste and Bologna (Italy). Device failure was assessed according to MVARC criteria. Patients were subsequently followed to additionally assess the patient success after 12 months. Results: Mean age was 67 ± 12 years, the mean Log-EuroSCORE was 23.4 ± 16.5%, and the mean LV end-diastolic volume index and ejection fraction (EF) were 112 ± 33 ml/m 2 and 30.6 ± 8.9%, respectively. At short-term evaluation, device failure was observed in 22 (29%) patients. Univariate predictors of device failure were LVEF, LV and left atrial volumes and anteroposterior mitral annulus diameter. Annulus dimension (OR 1.153, 95% CI 1.002–1.327, p  = 0.043) and LV end-diastolic volume (OR 1.024, 95% CI 1.000–1.049, p  = 0.049) were the only variables independently associated with the risk of device failure at the multivariate model. Conclusions: Pre-procedural anteroposterior mitral annulus diameter accurately predicted the risk of device failure after MitraClip in the setting of advanced HF. Its assessment might aid the selection of the best candidates to percutaneous correction of FMR. Highlights: Tools for identifying the optimal candidates to percutaneous correction of FMR are lacking Measures of extensive LV remodeling are associated with a high risk of early device failure Anteroposterior mitral annulus diameter is helpful to stratify the risk of early failure in HF patients with FMR Combined leaflet and annular percutaneous procedure should be tested to overcome the limits of Mitraclip alone